2004
DOI: 10.1590/s0074-02762004000700011
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the stability of the plasmids of Yersinia pestis cultures in vitro: impact on virulence

Abstract: Plasmid and chromosomal genes encode determinants of virulence for (Perry & Fetherston 1997, Parkhill et al. 2001, Deng et al. 2002. A 102-kb, unstable chromosomal area (locus pgm) is essential for Y. pestis virulence (Fetherston et al. 1992, Hinnebusch et al. 1996, Buchrieser et al. 1998.Typical strains of Y. pestis harbour three plasmids: pPst (9.5kb), encoding a plasminogen activator protease (Pla) (Sodeinde & Goguen, 1988; pFra (90kb), encoding a capsular protein Fraction 1 (F1) with antiphagocytic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…Leal-Balbino et al (2004 and Leal et al (2000) observed spontaneous alterations in the genome (plasmid and chromosomal) of Brazilian Y. pestis as a result of prolonged storage and handling in the laboratory. The stability of the PFGE profiles was investigated by the analysis of serial subcultures of three strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leal-Balbino et al (2004 and Leal et al (2000) observed spontaneous alterations in the genome (plasmid and chromosomal) of Brazilian Y. pestis as a result of prolonged storage and handling in the laboratory. The stability of the PFGE profiles was investigated by the analysis of serial subcultures of three strains.…”
Section: Discussionmentioning
confidence: 99%
“…Other strains were identified as P.Exu (laboratory location), and sequential number. Three unrelated strains (P.Exu 340, P.Peru 375 and P.CE 882) and 5 derived cultures obtained through multiple serial subcultures of the parental strains (Leal-Balbino et al, 2004) were included to assess the stability of PFGE profiles with subculture. The technique's reproducibility was evaluated by PFGE analysis of the strain P.PB 866 three times.…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
“…Alternatively, the strains could be inaccurate representatives of the original isolates, and these differences could be due to handling procedures during the prolonged storage of the strains in the laboratory since their isolation (Revazishvili et al, 2008;Vogler et al, 2011). Leal et al (2000) and Leal-Balbino et al (2004, 2006 observed spontaneous changes in the genome (both plasmid and chromosomal) of Brazilian Y. pestis following prolonged storage and laboratory handling. However, analysis of the 12 VNTR loci in the three parental strains and their derived cultures did not reveal changes in the studied regions, confirming their stability as previously observed (Adair et al, 2000;Keim et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen strains were isolated from an outbreak in 1986, which involved several municipalities in Planalto da Borborema, Paraíba State (de Almeida et al, 1989). Three unrelated strains (P. CE 882, P. Exu 340 and P. Peru 375) and 11 derived cultures obtained through multiple serial subcultures of the parental strains (Leal-Balbino et al, 2004) were included to assess in vitro VNTR stability. Figure 1 shows the localization of the Brazilian plague foci and origin of the strains.…”
Section: Bacterial Strains Studiedmentioning
confidence: 99%
“…Enzymatic defects cause incomplete partitioning during replication and decatenation and might result in the dimeric plasmid (14). We speculate that the unique plasmid architecture in Angola helps to guarantee a stable maintenance of both plasmids pMT and pPCP, as these two virulence plasmids are known to be unstable in Y. pestis (44). Indeed, other Pestoides isolates lack one of the two species-specific virulence plasmids (see Fig.…”
Section: Microevolution Of the Virulence Plasmidsmentioning
confidence: 97%